Validation of a paraoxon‐based method for measurement of paraoxonase (PON‐1) activity and establishment of RIs in horses. (25th March 2018) - Ruggerone, Beatrice; Bonelli, Francesca; Nocera, Irene; Paltrinieri, Saverio; Giordano, Alessia; Sgorbini, Micaela
Abstract : Background: Paraoxonase‐1 (PON‐1) is an antioxidant compound that is considered a negative acute phase protein. No information on the analytic performance of the paraoxon method for measuring PON‐1 in horse serum is available. Objectives: The aim of this study was to validate a paraoxon‐based method to measure PON‐1 in horses and to establish RIs in healthy horses and foals. Methods: Horses and foals classified as healthy after physical examination and routine biochemistry were used in the study. Serum PON‐1 activity was measured with an automated spectrophotometer and an enzymatic method validated in other species. After the analytic validation (precision, accuracy, interference studies), RIs were determined using the Reference Value Advisor software. The possible sex‐, age‐, and breed‐related differences were statistically investigated. Results: The healthy study population included 120 horses and 55 foals. The paraoxon‐based method was precise (CVs < 4.0%) and accurate ( P  < .001 in linearity under dilution and spike‐recovery testing) but was affected by interference from mild bilirubinemia, severe lipemia, and hemoglobinemia. The RIs recorded in the whole population were 38.1–80.8 U/mL. According to the Harris and Boyd test, it would be advisable to use separate RIs only for adult females and for Warmblood and Trotter adults. Conclusions: This study demonstrated that the analytic performances of the paraoxon‐based method for measurement of PON‐1 in horses are acceptable. The PON‐1 activity is lower in horses than in other domestic species. These results may provide a basis for further studies designed to establish whether healthy and sick horses can be correctly classified by using the PON‐1 assay.